Legal Characterization of the Challenges Faced by the Construction Industry During Covid-19 And Devaluation of the Egyptian Pound - Abuzaid, Riham (AUC Knowledge Fountain, 2022)
With all the challenges this past decade has inflicted on the economy on a global scale, Egypt had its share with two major events, starting with the Egyptian pound devaluation against the U.S dollar in 2016 and currently the emergence of the COVID-19 pandemic. These major events instigated the interference of the legal/contractual sectors in the construction market to find solutions that range from agreeable to stringent to protect the assets of their beneficiaries. Both events are impactful and require extensive analysis to determine and classify each situation. This thesis addresses the implementation of standard internationally acknowledged legislative acts used in Construction Contracts but are yet to experience practically for the first time in decades, whether under Hardship “Théorie de l'imprévision”, Force Majeure or Change in Legislation. The purpose of this thesis is to explore and analyse the various categories which these two events are under to enable them to survive during the countries’ sudden events. A detailed research is conducted to study the impact of the devaluation of the Egyptian pound and COVID-19 in the Construction projects in Egypt to categorize each event from a legal and Contractual perspective. Data is gathered based on a survey questionnaire to explore the opinions of 75 professionals working in the construction field. In addition, one-to-one interviews are conducted with selective members of the Construction/ Law industry followed by interviews with three different Construction Companies (Employer, Consultant and Contractor) to get their professional opinion on how COVID-19 and Devaluation of the Egyptian Pound are categorised from a legal perspective. Combining the findings from the survey and interviews along with the literature, the decision flowchart model is created. To validate the results obtained, the research findings along with the decision flowchart are used. The findings showed that the event of the devaluation of the Egyptian Pound is considered a Change in Legislation while the COVID-19 is considered a Hardship. The formulated Flowchart will be used as a guidance to enable users to categorize future similar events.